On Synergies of Schema Theory and Theory of Levels. A Perspective from Riepel’s Fonte and Monte - Folker Froebe (Zeitschrift der Gesellschaft für Musiktheorie)
Using specific examples I want to examine the extent to which the schema concept and the Schenkerian concept of hierarchical organized tonal structures may interlock or, at least, illuminate each other. In the first part I compare three 16- to 30-bar pieces by Mozart and Haydn with very similar middleground structures that are typically linked to the use of the Fonte schema after the double bar. The annotated graphs show correlations between schemata and Schenkerian prolongation figures at different structural levels. In the second part I discuss a piano piece by Robert Schumann in which a reminiscence on the galant Monte schema helps to establish a functionally coherent context that is very different from common tonal strategies. This analytical sketch could be a starting point to discuss the function and aesthetic significance of 18th century schemata in the ‘musical poetics’ of the 19th century.